2015
DOI: 10.4149/bll_2015_146
|View full text |Cite
|
Sign up to set email alerts
|

The effects of low and high doses of sugammadex on kidney tissue in streptozotocin-induced diabetic rats

Abstract: BACKGROUND: Sugammadex is primarily excreted via renal route. We investigated effects of low and high doses of sugammadex (16 mg/kg versus 96 mg/kg) on renal tissue samples of streptozotocin-induced diabetic rats. MATERIAL AND METHODS: Twenty-four Wistar albino rats were divided into 4 groups. Group C (control -0.9 % NaCl), Group DC (diabetes control; 55 mg/kg streptozotocin, IP, only), Group DR-16S (diabetes-rocuronium -16 mg sugammadex, IV.) and Group DR-96S (diabetes-rocuronium -96 mg sugammadex, IV). Renal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 23 publications
0
7
0
Order By: Relevance
“…Diabetic nephropathy predisposes to changes in kidney tissues, including inflammation, degeneration, necrosis, tubular dilatation, tubular cell degeneration, dilatation in Bowman’s space, tubular hyaline casts, and lymphocyte infiltration. In renal tissue samples, a significant increase in histopathological changes was found after sugammadex 96 mg/kg but not sugammadex 16 mg/kg treatment compared to diabetic control (Kip et al 2015 ). These results suggest that, at recommended doses, sugammadex does not significantly impact renal function (Bostan et al 2011 ), also in case of diabetic nephropathy (Kip et al 2015 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Diabetic nephropathy predisposes to changes in kidney tissues, including inflammation, degeneration, necrosis, tubular dilatation, tubular cell degeneration, dilatation in Bowman’s space, tubular hyaline casts, and lymphocyte infiltration. In renal tissue samples, a significant increase in histopathological changes was found after sugammadex 96 mg/kg but not sugammadex 16 mg/kg treatment compared to diabetic control (Kip et al 2015 ). These results suggest that, at recommended doses, sugammadex does not significantly impact renal function (Bostan et al 2011 ), also in case of diabetic nephropathy (Kip et al 2015 ).…”
Section: Discussionmentioning
confidence: 99%
“…In renal tissue samples, a significant increase in histopathological changes was found after sugammadex 96 mg/kg but not sugammadex 16 mg/kg treatment compared to diabetic control (Kip et al 2015 ). These results suggest that, at recommended doses, sugammadex does not significantly impact renal function (Bostan et al 2011 ), also in case of diabetic nephropathy (Kip et al 2015 ). In a dose-finding and safety study in adult patients, abnormal levels of N-acetyl-glucosaminidase were only found in 5 of 20 patients included in the intent-to-treat population and safety population (Sorgenfrei et al 2006 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Diabetic nephropathy predisposes to changes in kidney tissues including in ammation, degeneration, necrosis, tubular dilatation, tubular cell degeneration, dilatation in Bowman's space, tubular hyaline casts, and lymphocyte in ltration. In renal tissue samples, a signi cant increase in histopathological changes was found after sugammadex 96 mg/kg but not sugammadex 16 mg/kg treatment compared to diabetic control (Kip et al 2015). These results suggest that, at recommended doses, sugammadex doesn't signi cantly impact renal function (Bostan et al 2011), also in case of diabetic nephropathy (Kip et al 2015).…”
Section: Discussionmentioning
confidence: 75%
“…In renal tissue samples, a signi cant increase in histopathological changes was found after sugammadex 96 mg/kg but not sugammadex 16 mg/kg treatment compared to diabetic control (Kip et al 2015). These results suggest that, at recommended doses, sugammadex doesn't signi cantly impact renal function (Bostan et al 2011), also in case of diabetic nephropathy (Kip et al 2015). In a dose-nding and safety study in adult patients, abnormal levels of N-acetyl-glucosaminidase were only found in 5 of 20 patients included in the intent-totreat population and safety population (Sorgenfrei et al 2006).…”
Section: Discussionmentioning
confidence: 89%